Research of Variation Characteristic of Conveyor Belt of Vehicle Group Chain Conveyor based on Elastic Catenary Theory - Yaocheng Zhang; Yang Li (Jixie chuandong)
The vehicle group chain conveyor is new developed continuous conveying equipment for bulk materials. Compared with existing general belt conveyors, its load-bearing component-the conveyor belt has less tension when the entire machine is running. Based on elastic catenary theory, the tension change rule of the new type vehicle group chain conveyor belt is studied, a theoretical model of the belt tension change in the form of analysis is established, and deduces from it, the belt tension during the operation of the chain conveyor is obtained at last. The expression also proves the correctness of the catenary theory applied to this occasion.